2016
DOI: 10.14737/journal.jahp/2015/4.3.87.94
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study on Risk Factors Associated with Lameness of Working Donkeys in and around Hawassa, Ethiopia

Abstract: | A cross sectional study for risk analysis was undertaken on randomly selected working donkeys (n = 384) at the city Hawassa and its surroundings to estimate the prevalence of lameness. Among the lameness examined donkeys, all the lamed donkeys were subjected towards veterinary clinics for detailed characterization. Focus group discussion was carried out in 10 study sites with 60-70 donkey owners and cart-drivers. Locomotion scoring was recorded on a scale of (0-4; sound-non weight-bearing) at a walk of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(18 reference statements)
1
7
0
1
Order By: Relevance
“…In agreement to our results previous studies have also indicated the non significant associations of age for prevalence of bacterial diseases in farm animals (Kiros et al, 2016;Leghari et al, 2016). Shabbir et al (2015) have also reported no association of risk factors with prevalence of B. anthracis DNA in soil samples analyzed from Lahore, Pakistan.…”
Section: Journal Of Animal Health and Productionsupporting
confidence: 92%
“…In agreement to our results previous studies have also indicated the non significant associations of age for prevalence of bacterial diseases in farm animals (Kiros et al, 2016;Leghari et al, 2016). Shabbir et al (2015) have also reported no association of risk factors with prevalence of B. anthracis DNA in soil samples analyzed from Lahore, Pakistan.…”
Section: Journal Of Animal Health and Productionsupporting
confidence: 92%
“…While lameness is one of the most common health and welfare concerns in sport and pleasure horse populations [ 7 , 8 , 9 ], with significant implications for performance and survival [ 10 ], it is also a major issue in working equids in low- and middle-income countries [ 11 , 12 , 13 , 14 , 15 , 16 ]. Various factors associated with the presence or severity of lameness and gait abnormalities in working equids have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…As in other low and middle-income countries (LMICs), equid ownership is an important livelihood strategy for many families and therefore these animals’ health is paramount [2,3]. Lameness is one of the most common health problems observed in working equids, with a prevalence of up to 100% [4,5,6]. Independent of the initial aetiology of lameness, often first-line treatment involves rest and non-steroidal anti-inflammatory medicine.…”
Section: Introductionmentioning
confidence: 99%
“…However, this medical management in working equids is often compromised because they must work hard every day without the opportunity for time off and have limited access to animal healthcare services. Therefore, lameness is a major source of pain and compromised welfare in working equid populations [4,5,6,7]. In equids, lameness is often caused by foot pain; this is where the proverb “no foot, no horse” originates from.…”
Section: Introductionmentioning
confidence: 99%